I will never give up… Life stories of mature students in higher education - Gonçalves, Teresa (2014)
The Portuguese law 64/2006 allows mature students, older than 23, (M23) to access university, widening the participation of adult population in higher education. This paper is part of a research project focused on the experiences of non-traditional students in higher education. In this paper we analyse the stories of four mature students, with the aim to identify their motives for entering higher education; to understand their relationships with younger students; and to identify the main obstacles they face in their academic life.